Molecular characterization of ochratoxin a producing indigenous Aspergillus strains from poultry feed in Pakistan - Naz, Gull; Anjum, Aftab Ahmad; Ali, Tehreem; Nawaz, Muhammad; Iqbal, Sanaullah; Abbas, Mateen; Manzoor, Rabia (Universiti Kebangsaan Malaysia, 2023)
Ochratoxin A (OTA) is nephrocarcinogenic and immunosuppressive toxin and OTA producing molds contaminate the food crops. Isolation and identification of ochratoxin producing fungi was carried out from poultry feed samples (n=120) followed by preliminary confirmation through macroscopic and microscopic characteristics. Purified fungal isolates identified as Aspergillus 1842(91.68%) followed by Penicillium 91 (4.53%), Mucor 52 (2.58), Alternaria 7 (0.35%), Cladosporium 6 (0.29%), Fusarium 4 (0.199%) and unidentified (07). OTA production was confirmed through thin layer chromatography (TLC) followed by high performance liquid chromatography (HPLC). Only 41 isolates (2.22%) out of 1842 Aspergillus isolates were able to produce toxin. At genetic level, characterization was performed through polymerase chain reaction (PCR) using species specific gene primers. From 41 isolates 27, 9 and 5 were characterized as Aspergillus terreus, Aspergillus parasiticus, and Aspergillus ochraceus, respectively. Physical and chemical factors were optimized for OTA production. Under the effect of 37 °C temperature and 7.5 pH of Sabouraud dextrose broth (SDB) medium, higher toxin (969.45±.03 μg/mL) production was observed from ASPO-6 isolate. ASPO-4 isolate produce higher toxin amount in SDB medium with supplementation of maize 5%, wheat 1% and rice 3%. OTA stability was determined by adjusting standard concentration of 100 μg/mL in organic solvents (chloroform, acetonitrile and methanol) and organic solids. Least percentage log reduction in OTA concentration and stability of OTA was observed in opaque vials with chloroform and sucrose and transparent vials with sucrose after 6 months. OTA can be used as indigenous standard for identification of OTA from field samples.